Effect of Adding Minced Mackerel Fish (Scomberomorus commerson) Meat as A Protein Source in the Production of Cassava Crackers - Rifky Ardytiandi; Junianto Junianto; Kiki Haetami; Iis Rostini (Universitas Gadjah Mada, 2026)
The protein content of cassava crackers can be increased by adding minced mackerel. This research aims to determine the optimal percentage of mackerel fish mince to be added to the production of cassava crackers that yields the most preferred product, and to determine the proximate composition of the most preferred product. The method used was experimental: the production of cassava crackers with different levels of mackerel mince addition, comprising four treatments (0%; 7.5%; 10%; and 12.5%), with 20 semi-trained panellists as replicates, to determine the panellists’ preference for cassava crackers. The parameters observed in this study were the level of preference (hedonic) test, which was analysed using non-parametric statistics with the Friedman test, followed by multiple comparison tests and Bayes tests for decision making, as well as proximate tests to determine the moisture content, ash content, fat content, protein content, carbohydrate content, and calcium content. The results showed that cassava crackers with 10% mackerel meat added were the most preferred based on the Bayes method analysis and preference levels with average scores of 8.3 for appearance, 8.3 for aroma, 8.6 for taste, and 8 for texture. The proximate test results were moisture content 4.12%, ash content 3.41%, fat content 25.53%, protein content 4.51%, and carbohydrate content 72.26%, with an expandability of 59.22%.